The Pain is Far from Over: Exploring the Experiences of Parents and Adolescents Following Discharge After Inpatient Surgery - Dagg, William (Université d'Ottawa / University of Ottawa, 2019)
Background: Pain management is a major issue in post-operative care. Little is known about the pain management experiences of parents and adolescents following discharge from inpatient surgery. Studies examining pain outcomes following day surgery suggest that children often experience severe pain and parents are challenged in providing pain care. Objective: To explore the pain management experiences of parents and adolescents following discharge from hospital after inpatient surgery. Results: Thematic analysis found that parents and adolescents were challenged in providing pain care. School return was more difficult than anticipated yet parents and adolescents were unsure how to navigate pain at school. Discharge education focused on analgesic management, leaving participants to discover non-pharmacological strategies on their own. Conclusions: Recovery from post-operative pain following inpatient surgery is challenging; nurses and healthcare professionals need to better prepare parents and adolescents to meet pain care needs following discharge.
Keywords: Pediatric; Pain; Adolescent; Parent; Inpatient; Post-operative; Pain Management; Discharge